2006
DOI: 10.1016/j.jacc.2006.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Characterization of Myocardial Molecular Interventions by Integrated Positron Emission Tomography and Computed Tomography

Abstract: Integrated PET-CT has the potential to dissect cardiovascular biologic mechanisms from gene expression to physiologic function and morphology. The VEGF overexpression in healthy myocardium increases myocardial perfusion without significant up-regulation of alpha(v)beta3 integrin adhesion molecules early after the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…In clinical practice, the fusion images are typically used to map or localize the abnormal territory on emission images to the diseased vessel on coronary CTA (121). For research applications, hybrid imaging of radionuclide and CTA images is obtained for localization of radionuclide uptake (122,123). The fused images can be helpful to localize diseased regions but should not be the sole images used for diagnostic interpretation.…”
Section: Ctac and Emission Imagesmentioning
confidence: 99%
“…In clinical practice, the fusion images are typically used to map or localize the abnormal territory on emission images to the diseased vessel on coronary CTA (121). For research applications, hybrid imaging of radionuclide and CTA images is obtained for localization of radionuclide uptake (122,123). The fused images can be helpful to localize diseased regions but should not be the sole images used for diagnostic interpretation.…”
Section: Ctac and Emission Imagesmentioning
confidence: 99%
“…9,10 Only a few reports are available that describe molecular imaging of cardiac angiogenesis with nuclear 11,12 or optical 13 imaging.…”
mentioning
confidence: 99%
“…This type of reporter gene technology was used to detect the expression of VEGF 121 with PET/CT in porcine myocardium after adenoviral transfer (11). In that study, the authors demonstrated the value of integrated multimodal systems for detecting VEGF overexpression (with PET) and for localizing uptake to the myocardium (with CT).…”
Section: Nuclear Approachesmentioning
confidence: 99%